2016
DOI: 10.1007/s11481-016-9709-2
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Binge-like Ethanol Consumption by IL-10 Signaling in the Basolateral Amygdala

Abstract: Excessive ethanol consumption alters the neuroimmune system and particularly impacts the cytokine milieu of the CNS. Cytokine dysregulation has been shown to underlie addictive-like behaviors including alcohol abuse; however, many studies focus primarily on the proinflammatory cytokine profile and alcohol dependence. The current study furthers this research by determining the impact of excessive ethanol consumption on interleukin-10 (IL-10) and interleukin-4 (IL-4) activity in a model of non-dependent binge co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 52 publications
6
20
0
Order By: Relevance
“…Interestingly, this is consistent with studies finding innate immune signaling contributes to the development of AUD (Crews et al., 2017; de Timary et al., 2017). Innate immune signaling cytokines alter EtOH consumption (Marshall et al., 2017, 2017), and cytokine receptors contribute to stress‐induced EtOH consumption (Karlsson et al., 2017). Further, immune signaling molecules are increased in postmortem human alcoholic brain (Crews et al., 2017) and regulate preference for alcohol drinking in animal studies (Mayfield et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, this is consistent with studies finding innate immune signaling contributes to the development of AUD (Crews et al., 2017; de Timary et al., 2017). Innate immune signaling cytokines alter EtOH consumption (Marshall et al., 2017, 2017), and cytokine receptors contribute to stress‐induced EtOH consumption (Karlsson et al., 2017). Further, immune signaling molecules are increased in postmortem human alcoholic brain (Crews et al., 2017) and regulate preference for alcohol drinking in animal studies (Mayfield et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, reducing endotoxin release with antibiotics, probiotics, and drugs resulted in a loss of the stress hormone response, suggesting stress‐induced changes in blood endotoxin contribute to stress hormone responses (Ait‐Belgnaoui et al., 2012). Innate immune signaling cytokines also alter EtOH consumption (Marshall et al., 2016, 2017), and the cytokine receptors IL1R1 and TNFR1 contribute to stress‐induced EtOH consumption (Karlsson et al., 2017), suggesting the neuroimmune system may contribute to addiction. Cytokines also enhance stressful emotional states following alcohol withdrawal (Breese et al., 2008).…”
mentioning
confidence: 99%
“…Regarding the binge/intoxication, multiple immune interventions have been found to regulate alcohol consumption. Injection of the IL-1 receptor antagonist or the anti-inflammatory cytokine IL-10 into the basolateral amygdala reduced alcohol self-administration (Marshall et al, 2016a; Marshall et al, 2016c). Furthermore, microglial-inhibiting compounds blocked conditioned place preference to cocaine, suggesting a role for the neuroimmune system in the subjective reward of drugs (Northcutt et al, 2015).…”
Section: Innate Immune Molecules Mimic Addiction-like Behaviormentioning
confidence: 99%
“…Most notably, genomic studies in mice [5], rats [6], and humans [3,7,8] have identified several members of the Toll-like receptors (TLR) and interleukin-1/interleukin18 (IL-1/IL-18) receptor pathways in AUD [9,10]. Moreover, pharmacological [11][12][13], viral [14,15], or transgenic [2,9,11,[16][17][18][19][20] manipulation of the innate immune system leads to alterations of the ethanol-related behaviors in rodents. Collectively, this growing literature on innate immune responses critically contributing to the neurobiology of AUD [21][22][23] suggests that these pathways have high potential as targets for the development of new AUD therapeutic strategies [16,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%